Understanding breeding preferences among small-scale cattle producers: Implications for livestock improvement programmes - Mutenje, M.; Chipfupa, U.; Mupangwa, W.; Nyagumbo, I.; Manyawu, Godfrey J.; Chakoma, Irenie; Gwiriri, Lovemore C. (Elsevier, 2020)
Livestock production provides a pathway for improving livelihoods and reducing poverty in semi-arid tropical regions. However, this contribution has been affected by low livestock productivity. Most livestock programmes have also failed due to, among other things, the inability to understand the dynamics in smallholder breeding preferences. Using data from the sub-humid region in Zimbabwe, this paper sought to provide evidence on smallholder cattle breeding preferences and the implication on livestock improvement programmes. It applies the choice experiment approach to model farmer preferences for selected cattle breeding attributes. The results show three attributes that significantly affect breeding preferences. The attributes 'cow body condition score' and the 'useful life of a bull/semen' have a positive influence while 'artificial insemination/bull maintenance cost' negatively affects farmer preferences. This means farmers prefer breeding strategies which improve the nutrition of their cows, have a longer lifespan for the bull/semen and whose cost of breeding services is low. However, access to education and income affected these preferences. Education made farmers to make informed choices while higher incomes increased the propensity of investing in livestock breeding technologies. The findings also show that existing institutional arrangements in animal management and community grazing do not promote investment in livestock improvement. Thus, more attention should be given to improving animal nutritional management which includes promoting sustainable grazing schemes. There is also a need to provide affordable livestock breeding services through recruiting and training more artificial insemination service providers. Strong and effective institutions that provide incentives for collective participation are integral to any community-based livestock breeding programme. There is also a need to promote access to information and enhance farmers' knowledge and capacity in improved livestock management practices.